2021
DOI: 10.46592/turkager.2021.v02i01.013
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Effects of Various Fractions of Curcuma longa against Meloidogyne incognita (root knot nematodes)

Abstract: Parasitism is an important limiting factor responsible to cause damage to agricultural production. Plant parasitic root knot nematodes attack several economic crops in Pakistan. Plant- parasitic nematodes considerably add huge losses to economies in the top tomatoes crop producing countries throughout the world, instead of controlling the main pathogenic nematode species as usual; one of the innovative strategies to control plant-parasitic nematodes would be to manage diversity in communities in order to lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…According to Ulfa et al (2021), turmeric extract in various solvents significantly inhibited RKN egg hatching and root penetration but had no effect on RKN development or reproduction. Rashid et al (2021) used turmeric against M. incognita and found that while maximum mortality was achieved up to 20%, root gall severity and final nematode population were significantly suppressed, which is consistent with our findings. It was discovered that the use of turmeric is crucial for RKN management.…”
Section: Discussionsupporting
confidence: 91%
“…According to Ulfa et al (2021), turmeric extract in various solvents significantly inhibited RKN egg hatching and root penetration but had no effect on RKN development or reproduction. Rashid et al (2021) used turmeric against M. incognita and found that while maximum mortality was achieved up to 20%, root gall severity and final nematode population were significantly suppressed, which is consistent with our findings. It was discovered that the use of turmeric is crucial for RKN management.…”
Section: Discussionsupporting
confidence: 91%
“…al., 9 ; Neeraj et.al., 42 ; and Rashid et. al., 43 who reported suppressive effect on nematode activity and pathogenicity, using of Curcuma comosa which may be due to its high containing of nematicidal compounds on plant parasitic nematodes, such as alkaloids, diphenylheptanoids, phenolics, fatty acids, iso-thiocyanates, and thiophenics without any hazard effect on non-target organisms 5,43,44,45 . On the other hand, the enhancing in the plant growth parameters agreed with Yasmeen et.…”
Section: Discussionmentioning
confidence: 99%